Turk Arch Pediatrics 2022
DOI: 10.5152/turkarchpediatr.2022.21315
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Flexible Bronchoscopy in Difficult-to-treat Asthma from a Pediatric Pulmonology Perspective

Abstract: Objective Asthma is the most common chronic lung disease in childhood. Difficult-to-treat asthma is defined as the continuation of symptoms or attacks of patients despite step 4 or 5 of Global Initiative for Asthma therapy. In the differential diagnosis of these patients, flexible fiberoptic bronchoscopy is recommended to exclude other lung diseases. In this study, we aimed to examine the clinical and radiologic features and flexible fiberoptic bronchoscopy findings of patients referred to our ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Several retrospective studies have found that FB is a useful tool in children with persistent wheezing 34–36 or in “difficult to treat asthma” 37 with a definitive diagnosis made in 57%−85% of cases 34,35 . FB has also proven to be a valuable tool in the evaluation of infants with stridor (33.9% patients diagnosed with laryngomalacia, 49.5% of patients diagnosed with secondary airway lesions—tracheomalacia, tracheal compression, bronchomalacia, subglottic stenosis, 4.6% with subglottic haemangioma, 1.8% with subglottic web) 38 …”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies have found that FB is a useful tool in children with persistent wheezing 34–36 or in “difficult to treat asthma” 37 with a definitive diagnosis made in 57%−85% of cases 34,35 . FB has also proven to be a valuable tool in the evaluation of infants with stridor (33.9% patients diagnosed with laryngomalacia, 49.5% of patients diagnosed with secondary airway lesions—tracheomalacia, tracheal compression, bronchomalacia, subglottic stenosis, 4.6% with subglottic haemangioma, 1.8% with subglottic web) 38 …”
Section: Discussionmentioning
confidence: 99%
“…2,22,23 Bronchoscopy is an essential and safe method to diagnose and treat airway diseases in children. 8,24,25 Bronchoscope interventions facilitate cast clearance and access of inhaled drugs into the distal airways. 2,10,11 Recently, Kallam et al 12 reported that cryotherapy was useful and safe in bronchial casts that were refractory to conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment includes low‐dose oral macrolides, oral or ICS, aerosol tPA, and bronchoscopy to remove the casts 2,22,23 . Bronchoscopy is an essential and safe method to diagnose and treat airway diseases in children 8,24,25 . Bronchoscope interventions facilitate cast clearance and access of inhaled drugs into the distal airways 2,10,11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations